ONLINE MARKETING OF SMALL AND MEDIUM ENTERPRISES IN SAMAR, PHILIPPINES - Patimo, Donald; Dollado, Rodolfo (IJBLE Scientific Publications Community Inc., 2021)
Marketing is considered an important strategy in attaining the business objectives. With this, efficient tools are significant to achieve those objectives. Today, the Internet and web technologies facilitate efficient and effective marketing activities. Literatures showed that many business organizations are using online marketing to promote and advertise their products and services. The importance of online marketing has prompted the researchers to conduct this study. This study aimed to assess the status of the Small and Medium Enterprises (SMEs) in the province of Samar in adopting online marketing. It employed the descriptive research design. The questionnaire was used as the primary research instrument to gather data. The respondents of the study included the business owners and operators of Small and Medium Enterprises (SMEs) and online customers in the province of Samar. The results showed that the products/services offered by SMEs were mostly food products, clothes, shoes, jewelry, and groceries. The commonly used marketing tool by SMEs was tarpaulin. The most felt problem encountered by SMEs in the marketing of products was financial issues. Moreover, the majority of the SMEs revealed that they were likely to adopt online marketing. Overall, the results showed that there is a presence of strong demand for online marketing in the province of Samar. Therefore, SMEs in Samar are willing to adopt online marketing despite the uncertainties and problems identified in the study.